The Concomitant Therapy of Direct Oral Anticoagulants with Amiodarone in Atrial Fibrillation: A Meta-analysis - Kazuhiko Kido PharmD, PhD; Mikiko Shimizu PhD; Tsuyoshi Shiga MD, PhD; Masayuki Hashiguchi PhD (Journal of Cardiovascular Pharmacology and Therapeutics)
Background The concomitant therapy of amiodarone with direct oral anticoagulants (DOACs) significantly increases the concentrations of DOACs and may increase the bleeding risks. Multiple real-world studies compared the concomitant therapy of amiodarone and DOACs versus the DOAC alone, but their main findings were contradictory. Methods A meta-analysis compared the concomitant therapy of amiodarone and DOACs versus DOACs monotherapy. Database searches through May 1, 2025, were performed. The primary outcome was major bleeding. The secondary outcomes included stroke or systemic embolism, any bleeding, all-cause mortality, gastrointestinal bleeding, and intracranial bleeding. Results This meta-analysis included a total of nine studies. There were no significant differences in major bleeding between the concomitant therapy of amiodarone and DOAC and DOAC monotherapy groups (OR 1.12; 95% CI 0.98, 1.27; P  = .09; I 2  = 64%). No significant differences in any bleeding (OR 1.18; 95% CI 0.88, 1.57; P  = .27; I 2  = 77%), gastrointestinal bleeding (OR 0.97; 95% CI 0.84, 1.11; P  = .65; I 2  = 56%), and intracranial bleeding (OR 1.14; 95% CI 1.00, 1.30; P  = .05; I 2  = 32%) were also found between the two groups. No significant differences in stroke or systemic embolism were found between the two groups (OR 0.86; 95% CI 0.74, 1.00; P  = .05; I 2  = 34%). Conclusion and Relevance The concomitant therapy of amiodarone and DOACs did not significantly increase the bleeding risks or decrease the risk of stroke or systemic embolism compared to the DOAC monotherapy. The drug-drug interactions between amiodarone and DOACs may not be clinically significant.